2022
DOI: 10.1001/jama.2022.9451
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intraoperative Handovers of Anesthesia Care on Mortality, Readmission, or Postoperative Complications Among Adults

Abstract: IMPORTANCEIntraoperative handovers of anesthesia care are common. Handovers might improve care by reducing physician fatigue, but there is also an inherent risk of losing critical information. Large observational analyses report associations between handover of anesthesia care and adverse events, including higher mortality.OBJECTIVE To determine the effect of handovers of anesthesia care on postoperative morbidity and mortality. DESIGN, SETTING, AND PARTICIPANTSThis was a parallel-group, randomized clinical tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…There are up to 300 million surgical procedures annually in the world [ 1 ]. About 10–50% of surgical patients suffer continuous postsurgical pain [ 2 ], of which, about 2–10% is severe pain that lasts for at least one year [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are up to 300 million surgical procedures annually in the world [ 1 ]. About 10–50% of surgical patients suffer continuous postsurgical pain [ 2 ], of which, about 2–10% is severe pain that lasts for at least one year [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…First, we believe that the negative findings in this study should be interpreted in light of the fact that continuity of care was preserved in most cases via the supervising anesthesiologist even after cases were handed over between anesthesia trainees . This definition of complete handover differs from those used in prior studies, in which an attending anesthesiologist transitioned patient care to another attending anesthesiologist and then was no longer available .…”
mentioning
confidence: 66%
“…This definition of complete handover differs from those used in prior studies, in which an attending anesthesiologist transitioned patient care to another attending anesthesiologist and then was no longer available . The continuity of supervisory anesthesia care in this study may have served as a buffer that prevented negative outcomes. Although the primary analysis found no differences in the composite outcome, the adjusted analysis, as recommended for randomization stratification factors, showed that 1 handover of care had an odds ratio of 1.16 for the 30-day composite primary outcome of all-cause mortality, hospital readmission, or serious postoperative complications.…”
mentioning
confidence: 85%
See 2 more Smart Citations